Characterization of mangrove species located in the vicinity of the "Almirante Padilla" Naval Cadet School - Mendoza-Pérez, Cristhian; Vitola-Quintero, Marena; López-Osorio, Luis; Rodríguez-Ortiz, Johan (EFIM Ediciones, 2019)
In the present work, the characterization of the mangrove species that are present in the Island of Manzanillo is included, as well as an analysis of the distribution of the same in the study area. It is worth mentioning that this ecosystem is widely biodiverse and important for the marine and terrestrial environment, but due to the anthropic eﬀect accentuated by diﬀerent activities on the island, its conditions are not the best. Both the fauna and the ﬂora of the mangrove forest are aﬀected when the biotic or abiotic factors change, either by human action or natural situations, that is why, in the framework of this work the benefts of the ecosystem for the environment were reﬂected environment and the community in general, which makes it an object of preservation and sustainable use for the National Navy, according to what is stated in its research lines more specifcally “Maritime Interests”, due to this, the investigation focused on identifying the mangrove species present around the Isle of Manzanillo and its distribution. The above through feld sampling according to the methodology of Ulloa-Delgado et al. (1998), as well as the calculation and analysis of the Curtis & Mcintosh Species Importance Value Index (1950).